ERECTILE DYSFUNCTION: CAUSES, TREATMENT, AND PREVENTION (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
Erectile dysfunction (ED), commonly referred to as impotence, is the inability to achieve or maintain an erection sufficient for satisfactory sexual performance. It is a prevalent condition affecting millions of men worldwide, particularly those over the age of 40. However, younger men can also experience ED due to various psychological and physiological factors. This article explores the causes, treatments, and preventive measures for erectile dysfunction.